Expanding the Scope of Community Pharmacy Practice in Nova Scotia: Impacts on Provincial COVID-19 Response - Ingrid Sketris; Andrea Bishop; Tasha Ramsey; Jennifer Isenor; Chiranjeev Sanyal (Health Reform Observer - Observatoire des Réformes de Santé, 2023)
Nova Scotia has expanded the scope of practice for community pharmacists by allowing, among other changes, pharmacist prescribing under specific circumstances (2011) and administration of drugs by injection (2013), thereby alleviating stress on the health system. Due to these progressive expansions in community pharmacy scope of practice, Nova Scotia community pharmacy personnel (about 1,500 pharmacists and 246 technicians working in 315 pharmacies) were rapidly able to play key roles in the province’s response to the COVID-19 pandemic. Community pharmacies provided medicines, medical devices, personal protective equipment, hand hygiene solutions, thermometers, and pulse oximeters to patients and the public. In addition, they have responded to patients’ COVID-19-related needs by treating symptoms; providing referrals; discussing the benefits and risks of COVID-19 vaccines and administering them; making nirmatrelvir/ritonavir assessments; and addressing vaccine hesitancy and the spread of misinformation about COVID-19. Moreover, as in some other provinces, community pharmacists in Nova Scotia have played a leading role in delivering COVID-19 vaccines from almost the start of the vaccination campaign in December 2020. Their role expanded further in May 2022, when pharmacists were granted prescribing authority for inhaled budesonide in accordance with the provincial protocol to treat mild SARS-CoV-2 respiratory symptoms.